Optimalisasi Pemahaman Hukum Tenaga Medis dan Tenaga Kesehatan dalam Perlindungan Data Pribadi Pasien di Rumah Sakit - Daddy Fahmanadie; Yulia Audina Sukmawan; Ifrani Ifrani; Muhammad Topan; Dadang Abdullah; M. Ali Amrin; Abdul Halim Barakatullah; Rike Julian Syafrilla; Denok Kusuma Wardani (Pusat Riset dan Inovasi Nasional, 2025)
The development of information technology in the healthcare sector brings significant benefits for improving services, but also poses serious challenges related to the protection of patient personal data. The prevalence of medical data leaks demonstrates weak security systems and a low level of understanding among healthcare workers regarding the legal and ethical aspects of data management. This study aims to improve the legal understanding of medical and healthcare workers in protecting patient personal data through the Compulsory Lecturer Service Program (PDWA) at a hospital in Banjarmasin City. The method used was participatory outreach, delivering materials on regulations, data governance, and professional ethics, as well as quantitative evaluation through pre- and post-tests. The results showed a gap in initial knowledge, but after the outreach, there was a significant increase in legal understanding, professional attitudes, and ethical awareness among participants. This program also encouraged the formation of a work culture that better respects patient privacy and strengthens hospital institutional governance, thereby increasing public trust in healthcare services. The implications of this activity are the importance of ongoing training, strengthening internal regulations, and developing a secure digital infrastructure to minimize the risk of data leaks. Thus, patient personal data protection can be implemented optimally and sustainably in the hospital environment.